AN ANALYSIS OF GENERATOR MAINTENANCE (GENGSET) BASED ON TPM (TOTAL PRODUCTIVE MAINTENANCE) METHOD AT PT. LEONG AYAM ONE PRIMADONA - Siregar, Fakhri Alamsyah; Tarigan , Adisastra Pengalaman (INFOKUM, 2022)
In the current era of globalization, a gengset is needed as a backup source of electrical energy, because the gengset can be a substitute for electric current sourced from PLN. And in maintaining quality, one of the important factors that must be considered is the problem of machine maintenance (maintenance). In connection with this, the party handling the maintenance problem must be able to find the best maintenance system to be able to minimize the number of machine breakdowns and repair or maintenance costs incurred. The purpose of this research is to understand the principles and workings of the gengset used by PT Leong Ayam Satu Primadona, identify problems that occur in the gengset, and determine the amount of horse power from the gengset. And the results of the research that has been done, as for the calculation of power (kVA) generator operations in May, June and July of 2022 diperolwh average power in May amounted to 44.84 kVA, June amounted to 44.84 kVA, and July amounted to 44.36 kVA. And the total use of diesel fuel in May was 47,082 liters, for June as much as 47,124 liters, and in July as much as 46,578 liters.